KONSEP HIDÂYAH DALAM TAFSÎR AL-QUR’ÂN BÎ AL-IMLÂ’ KARYA KIAI ZAINÎ MUN’ÎM - Khairul Muttaqin (IAIN Madura, 2020)
At the Islamic Boarding School of Nurul Jadid in Paiton Probolinggo there is a work of interpretation composed by the founder and the first caretaker of Islamic Boarding School of Nurul Jadid in Paiton Probolinggo. The work of interpretation of the archipelago was composed by Zainî Mun'îm. The commentary is entitled Tafsîr al-Qur’ân bi al-Imlâ’. Named with Tafsîr al-Qur’ân bi al-Imlâ’ because initially this interpretation is an interpretation taught by Zainî Mun'im to the Students of the Islamic Boarding School of Nurul Jadid by way of dictation (Imlâ’) and then the Student of Islamic Boarding School Nurul Jadid recorded and codified the interpretation. In addition, this commentary is also called Tafsîr Sûrah al-Fâtihah . This commentary is named Tafsîr Sûrah al-Fâtihah because in it only discusses the interpretation of the al-Fâtihah only. The purpose of the writing of this scientific paper is to provide additional insight and inform the readers about the work of Tafsîr archipelago composed by the founder and the first caretaker of Islamic Boarding School of Nurul Jadid in Paiton Probolinggo is Zainî Mun'îm. The method used in writing this scientific paper is library research. in this scientific paper the author collects information from books explaining about Tafsîr al-Qur’ân bi al-Imlâ’ or Tafsîr Sûrah al-Fâtihah and analyzes the contents of the book of interpretation. In this scientific work the author tries to describe the form of interpretation, interpretation method, interpretation style and content of Tafsîr al-Qur’ân bi al-Imlâ’ or Tafsîr Sûrah al-Fâtihah . By knowing the form interpretation, interpretation method, interpretation style and the content of Tafsîr al-Qur’ân bi al-Imlâ’ or Tafsîr Sûrah al-Fâtihah then the reader can understand more detail about characteristics of Tafsîr al-Qur’ân bi al-Imlâ’ or Tafsîr Sûrah al-Fâtihah. Zainî Mun'îm explained in Tafsîr al-Qur'ân bi al-Imlâ’ that guidance is divided into 5 parts namely hidayah ilham (guidance in inspiration), hidayah al-hawas (guidance in the form of senses), hidayah al-`uqul (guidance in the form of reason), hidayah al-adyan wa al-syara'i` (instructions in the form of religion and shari'ah) and hidayah al-fi'iyyah (instructions towards the good). The concept of hidayah as in the Tafsîr al-Qur'ân bi al-Imlâ’ is also found in Tafsîr al-Marâghî, Tafsîr al-Manâr and Tafsîr al-Munîr. From the year of compilation it was not possible if Zaini Mun'im quoted Tafsîr al-Manâr and Tafsîr al-Munîr because they had already been prepared. The thought of Zaini Mun'im was quoted in many cases from Tafsîr al-Marâghî which was composed by Musthafâ al-Marâghî.